Komunikasi Naratif Pesan Politik dalam Video Youtube PDP: Podcast Depan Pintu - Ayu Eva Utami; Didi Permadi; Ike Desi Florina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Digital media such as YouTube has become a new means of conveying social and political issues narratively. The Front Door Podcast (PDP) hosted by Kaesang Pangarep utilizes narrative communication as an approach to educate the public in a light and informative style. This study aims to analyze the narrative communication in Podcasts, as well as the impact of the content presented to the audience. The research method used is descriptive qualitative with observation and content analysis techniques which use Tzvetan Todorov's narrative theory with three stages: initial situation, conflict, and resolution. The results of the study show that the narrative in the PDP discusses a lot about the world of politics. This can attract the idea of the audience so that they can think positively and be able to educate and entertain the audience, as well as improving and also having educational value and shaping people's perspective on social and political issues.